The making of feudal agricultures? - Barceló, Miquel; Sigaut, François (Transformation of the Roman world, 2004)
Was there a discernible set of changes in the techniques of arable farming, animal husbandry and their associated technologies at the end of antiquity which marked a clear break with an established 'ancient world economy' and ushered in the 'new agricultures' of the early middle ages? Were such changes not already visible in antiquity? And what was the impact of political, economic, social and environmental change in these processes? The 6 papers in this volume reject simple evolutionary models charting progress from "protohistory" to the "Roman period" to the "Dark Ages" to the "Middle Ages" and insisted rather on the notion of inheritance, so that the farming economy laid down in protohistoric times continued to exist during the early Middle Ages. The collapse of a capitalistic commercial economy of the later Roman Empire though accompanied by political and military crises did not entail a regression of the farming economy. The growth in farming in the 8th - 9th C, resting on a demographic increase combined with intensive land clearance episodes, owed much to the preceding centuries: the change resides more in an intensification than in the introduction of new features. With contributions by Pascal Reigniez, Catherine Rommelaere, Georges Raepsaet, G. Comet, Aline Durand and Philippe Leveau.